2010
DOI: 10.1016/j.aorn.2010.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Atrial Myxomas

Abstract: Myxomas are the most common form of benign cardiac tumors; these tumors occur primarily in the atria. Most myxomas are idiopathic in origin, but in rare cases, patients have a family history of myxomas. Although these tumors are benign, myxomas have the potential to cause serious complications, including embolic events and partial or complete obstruction of intracardiac blood flow. Currently, there is no effective medical treatment, and surgical excision of the tumor is necessary. Typically, surgical resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 9 publications
1
26
0
2
Order By: Relevance
“…Primary tumors of the heart are relatively rare and the most common are atrial myxomas which account for 50% of all primary cardiac tumors [1]. Left atrial myxoma in pregnant patients is extremely rare, only 51 cases being reported in the most recent literature review in 2015 [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary tumors of the heart are relatively rare and the most common are atrial myxomas which account for 50% of all primary cardiac tumors [1]. Left atrial myxoma in pregnant patients is extremely rare, only 51 cases being reported in the most recent literature review in 2015 [2].…”
Section: Discussionmentioning
confidence: 99%
“…It occurs mostly in women and is sometimes detected during pregnancy [1]. Cardiac myxoma in pregnant woman is extremely rare; the most recent literature review published in 2015 reported only 51 cases from 44 publications, and its management is also very difficult [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prompt surgical excision must be performed as soon as the diagnosis is confirmed because of the high risk of new embolic complications or sudden death 1). However, postoperative thromboembolic events occur infrequently, and atrial arrhythmias are the most common complications after surgery for myxoma 5)6)7)8). Although myxomatous fragments of a tumor or thrombi at the tumor surface may dislodge during surgery, the occurrence of atrial fibrillation is the main reason for postoperative thromboembolic complications 9).…”
Section: Discussionmentioning
confidence: 99%
“…Roughly, three quarters of cardiac tumors are benign and remainders are malignant; half of benign cardiac tumors are myxomas [1,3]. Although Cardiac Myxomas (CM) are benign tumors but they are a major cause of patient morbidity and mortality, due to impairment of cardiac dynamics and their thromboembolic potential [3,4].…”
Section: Introductionmentioning
confidence: 99%